Relativity analysis on wireless value-added services market and SP regulation - LI Da-chuan1; SUN Hong-bin1; XIN Zhan-hong1 (Tongxin xuebao)
Number, CI （corporation image） and creativity of SP （services provider）, set up a theory model on WVAS（wireless value-added services） market and SP regulation, to research regulation’s impact on SP market were analyed. The model shows that the impact can be classified to four areas: free area, loose area, rational area and restrict area. Through analyzing financial impact of regulation via SP, finds the importance of reinforcing regulation. The last part gives some suggestions by model analysis and experience analysis.